2013
DOI: 10.1212/wnl.0b013e31827f0efc
|View full text |Cite
|
Sign up to set email alerts
|

Birth hospitalization in mothers with multiple sclerosis and their newborns

Abstract: Objective: To compare the duration of birth hospitalization in mothers with multiple sclerosis (MS) and their newborns relative to the general population and to investigate the impact of MS-related clinical factors on the length of birth hospitalization stays.Methods: Data from the British Columbia Perinatal Database Registry and the British Columbia MS database were linked in this retrospective cohort study. The duration of birth hospitalization in mothers with MS and their newborns (n 5 432) were compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 22 publications
2
26
0
Order By: Relevance
“…Women with MS do not seem to have a higher risk of obstetrical/neonatal complications [10,11,25], although there are some contrasting reports [2,8], and they may undergo planned CDs more frequently compared to the general population, [10] especially if they have a higher disability [11]. The diagnosis of MS alone, should not lead to the decision of a CD, which should be considered should there be concern about spasticity, neuromuscular perineal weakness or exhaustion.…”
Section: Mode Of Deliverymentioning
confidence: 99%
“…Women with MS do not seem to have a higher risk of obstetrical/neonatal complications [10,11,25], although there are some contrasting reports [2,8], and they may undergo planned CDs more frequently compared to the general population, [10] especially if they have a higher disability [11]. The diagnosis of MS alone, should not lead to the decision of a CD, which should be considered should there be concern about spasticity, neuromuscular perineal weakness or exhaustion.…”
Section: Mode Of Deliverymentioning
confidence: 99%
“…81–83 A trend for more frequent labor induction in women with greater disability warrants further investigation. 82 Neither epidural anesthesia 84,85 nor cesarean section 85 has been associated with adverse effects on delivery or postpartum MS course.…”
Section: Delivery and Post-pregnancymentioning
confidence: 99%
“…While some studies have shown a higher rate of assisted vaginal deliveries, for example requiring induction and slower progression of labor, 5 there is evidence to suggest that mothers and newborns do equally well and do not have longer birth hospitalizations that non-MS counterparts, even when accounting for longer disease duration and increased disability. 15 Our study has several limitations. As a single-center pilot study conducted in an urban area, our results might not be broadly generalizable to the MS population.…”
Section: Discussionmentioning
confidence: 91%